2019
DOI: 10.1098/rstb.2018.0032
|View full text |Cite
|
Sign up to set email alerts
|

Would a robot trust you? Developmental robotics model of trust and theory of mind

Abstract: Trust is a critical issue in human–robot interactions: as robotic systems gain complexity, it becomes crucial for them to be able to blend into our society by maximizing their acceptability and reliability. Various studies have examined how trust is attributed by people to robots, but fewer have investigated the opposite scenario, where a robot is the trustor and a human is the trustee. The ability for an agent to evaluate the trustworthiness of its sources of information is particularly useful in joint task s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…This circular behavior would make the human-robot relationship increasingly ecological and, ultimately, trustful. Starting, for example, from the architectural model designed by Vinanzi et al (2019), in which the robots' trust in an informant varied as a function ToM, the present findings clearly indicate further psychological factors that may be integrated in the robot to design the robot's trust in the human at different developmental levels. Recent technical and theoretical achievements in the field of social robotics have encouraged researchers to develop social robots as tutors and learning companions for children (e.g.…”
Section: Conclusion Limitations and Future Directionsmentioning
confidence: 58%
See 1 more Smart Citation
“…This circular behavior would make the human-robot relationship increasingly ecological and, ultimately, trustful. Starting, for example, from the architectural model designed by Vinanzi et al (2019), in which the robots' trust in an informant varied as a function ToM, the present findings clearly indicate further psychological factors that may be integrated in the robot to design the robot's trust in the human at different developmental levels. Recent technical and theoretical achievements in the field of social robotics have encouraged researchers to develop social robots as tutors and learning companions for children (e.g.…”
Section: Conclusion Limitations and Future Directionsmentioning
confidence: 58%
“…Developmental Robotics (Cangelosi and Schlesinger, 2015). For example, Vinanzi et al (2019) have proposed an artificial cognitive architecture to simulate human decision making in the robot by using concepts from developmental theories, such as Theory of Mind (ToM). From this perspective, the implementation of an artificial architecture, together with an understanding of the human's response to the behavior of a robot within a relational context, aims to shed light on the processes involved in establishing a relationship with robotic agents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of the literature by Marchetti et al (2018) showed that different physical characteristics of HSRs may significantly affect the quality of interaction between humans and robots at different ages. The construction of robots that integrate and expand the specific biological abilities of our species led to two different directions in robotic development based on different, though related, theoretical perspectives: developmental cybernetics (DC; Itakura, 2008 ; Itakura et al, 2008 ; Moriguchi et al, 2011 ; Kannegiesser et al, 2015 ; Okanda et al, 2018 ; Di Dio et al, 2019 ; Wang et al, 2020 ; Manzi et al, 2020a ) and developmental robotics (DR; De La Cruz et al, 2014 ; Cangelosi and Schlesinger, 2015 , 2018 ; Lyon et al, 2016 ; Morse and Cangelosi, 2017 ; Vinanzi et al, 2019 ; Zhong et al, 2019 ; Di Dio et al, 2020a , b ). The first perspective (DC) consists of creating a human-like system, by simulating human psychological processes and prosthetic functions in the robot (enhancing the function and lifestyle of persons) to observe people’s behavioral response toward the robot.…”
Section: Introductionmentioning
confidence: 99%
“…It is conceivable that machines made self-aware via inner speech implementation could engage in Theory-of-Mind, especially since the former most likely is implicated in the latter (Fernyhough and Meins, 2009 ). However, the precise operations required for the development of artificial Theory of Mind remain elusive at present—but see Vinanzi et al ( 2019 ) and Winfield ( 2018 ), among others.…”
Section: Discussionmentioning
confidence: 99%